2014
DOI: 10.1111/infa.12054
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Responsiveness and the Development of Directed Vocalizing in Social Interactions

Abstract: For effective communication, infants must develop the phonology of sounds and the ability to use vocalizations in social interactions. Few studies have examined the development of the pragmatic use of prelinguistic vocalizations, possibly because gestures are considered hallmarks of early pragmatic skill. The current study investigated infant vocal production and maternal responsiveness to examine the relationship between infant and maternal behavior in the development of infants' vocal communication. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(137 citation statements)
references
References 83 publications
5
108
0
6
Order By: Relevance
“…Likewise, research on infants' gesture production has shown that communicative gestures (e.g., iconic and pointing gestures) signal intentional communication (Bates et al, 1979;Bavin et al, 2008;Caselli, Rinaldi, Stefanini, & Volterra, 2012) and that pointing gestures with a declarative intention are a good predictor of the emergence of verbal language (Colonnesi, Stams, Koster, & Noom, 2010). On the other hand, literature on speech development has also documented that acoustic measures of early infants' vocalizations vary depending according to their communicative intentionality (Esteve-Gibert & Prieto, 2014) and that vocalizations coordinated with gaze directed at the referent affect adult-infant social interactions and support language learning (Goldstein, Schwade, Briesch, & Syal, 2010;Gros-Louis, West, & King, 2014). While some studies with slightly older infants have shown that one particular use of supplementary gesture-speech combinations -that in which the gesture modality conveys a different meaning than the one conveyed by speech -predicts the onset of grammatical development (Capirci, Iverson, Pizzuto, & Volterra, 1996;Iverson & Goldin-Meadow, 2005;Özç aliskan & Goldin-Meadow, 2005;Pizzuto, Capobianco, & Devescovi, 2005;Rowe & GoldinMeadow, 2009), the emergence of simultaneous gesture-speech combinations (i.e., gesture co-occurring with speech to express the same meaning) and their relation to later language development has not been analyzed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, research on infants' gesture production has shown that communicative gestures (e.g., iconic and pointing gestures) signal intentional communication (Bates et al, 1979;Bavin et al, 2008;Caselli, Rinaldi, Stefanini, & Volterra, 2012) and that pointing gestures with a declarative intention are a good predictor of the emergence of verbal language (Colonnesi, Stams, Koster, & Noom, 2010). On the other hand, literature on speech development has also documented that acoustic measures of early infants' vocalizations vary depending according to their communicative intentionality (Esteve-Gibert & Prieto, 2014) and that vocalizations coordinated with gaze directed at the referent affect adult-infant social interactions and support language learning (Goldstein, Schwade, Briesch, & Syal, 2010;Gros-Louis, West, & King, 2014). While some studies with slightly older infants have shown that one particular use of supplementary gesture-speech combinations -that in which the gesture modality conveys a different meaning than the one conveyed by speech -predicts the onset of grammatical development (Capirci, Iverson, Pizzuto, & Volterra, 1996;Iverson & Goldin-Meadow, 2005;Özç aliskan & Goldin-Meadow, 2005;Pizzuto, Capobianco, & Devescovi, 2005;Rowe & GoldinMeadow, 2009), the emergence of simultaneous gesture-speech combinations (i.e., gesture co-occurring with speech to express the same meaning) and their relation to later language development has not been analyzed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the time window between infants' and adults' behaviors was chosen to be 1 second as a criterion of contingency (Bigelow, 1996;Bigelow & Rochat, 2006;Bigelow & Power, 2014;Kochanska & Aksan, 2004;Lohaus et al, 2005). In a number of experiments, the time window was longer: 2 seconds (Mcquaid et al, 2009;Bornstein et al, 2015;Gros-Louis, West, & King, 2014) or 5 seconds (Baumwell, Tamis-LeMonda, & Bornstein, 1997;45 Olson, Bates, & Bayles, 1984) following infants' actions. In some cases, the time window used as a criterion of contingency was not specified (Goldstein, King, & West, 2003;Bornstein & Tamis-LeMonda, 1989).…”
Section: Theoretical Constructmentioning
confidence: 99%
“…Such behaviors included smiles and vocalizations (Bigelow & Rochat, 2006;Mcquaid et al, 2009;Bornstein et al, 2015), where vocalizations sometimes were restricted to non-distress (Bigelow & Power, 2014) or positive (Kochanska & Aksan, 2004) and directed at objects or interlocutors (Baumwell, Tamis-LeMonda, & Bornstein, 1997;Gros-Louis, West, & King, 2014).…”
Section: Theoretical Constructmentioning
confidence: 99%
See 1 more Smart Citation
“…Kontrol grubunda da son test puan ortalamasına göre ön test puan ortalamasındaki değişim istatistiksel olarak anlamsız bulunmuştur (p=0.572; p>0.05). Deney grubundaki bebeklerin dil gelişimlerindeki artışın önemsiz olması sonucu, anne-bebek etkileşimsel davranışlarının bebeğin dil gelişimini olumlu etkilediğini ortaya koyan bazı araştırmalarla uyumlu görünmezken (Magagna, 2013;Gros-Louis, West ve King, 2014); anne-bebek etkileşimine ilişkin davranışların bebeğin dil gelişimini artırmada etkili olmadığı araştırma bulgularıyla paralellik göstermektedir (Capirci, Caselli, Iverson, Pizzuto ve Volterra, 2002). Araştırmada Ev Merkezli Anne-Bebek Etkileşim Programı'nın bebeğin dil gelişiminin artırılmasında herhangi bir etki oluşturmaması, programın kapsamı ve niteliği göz önüne alınarak açıklanabilir.…”
Section: Verilerin Analiziunclassified